História da Brigada Militar, pelas páginas da Revista Pindorama - Silva, Amanda Siqueira da (2013)
The Pindorama magazine emerged in recent years Borgismo in Rio Grande do Sul, within the Rio Grande Republican Party crisis and political change in the country. The magazine came within the Military Brigade, with the support of their commander, however this was a private publication of two lieutenants, which had the intention of remembering the great military achievements of the institution, demonstrating a concern for the history of BM would not be forgotten, as well as reinforced the commitment of BM with the ideology of PRR . The Military Brigade was established in 1892 and since then has been sustaining the political hegemony of the PRR in Rio Grande do Sul, acted in defense of these in the Federalist Revolution (1893), Assisista in Revolt (1923) and uprisings against the lieutenants (1924 to 1926). During his training, received a military training mission by the National Army, which later led to a close proximity between the Forces, the Military Brigade received strong military rigging, allowing this to become a regional army with several performances in support of castilhista republican ideals. Analyze Pindorama magazine possible to recall the history of the Military Brigade through various articles; understand the vision of a portion of the members of the brigade, about how they saw in society, their professional aspirations, their concerns about the possible changes that drew because the end the borgismo, the desire to be a military brigade beat militarily, through the continuing education of its members and to attempt to create a service in its own aviation; identification with the Republican ideology Castilhista and the role that particular group has within the institution: genuine and legitimate defenders of republican order in Rio Grande do Sul. Pindorama through its various pages emphasized the firepower of the Military Brigade, as well as political participation during this period of the First Republic in Brazil